Christ's Presence in the Poor and the Church: A Traditionalist Liberation Theology. Issue 3 (August 2019) - McCullough, Ross
This paper argues that central claims about the poor in liberation theology do not displace traditional claims about the centrality of the Church but are a natural outworking of them. Christ is present in the poor first in the sense that Christ is present prior to and as preparation for justification, working to overcome our infirmities; Christ is present second in the sense that the poor are God's special instrument of salvation. Neither manner of being present relies on the rethinking of nature and grace in the 20th century that is sometimes made foundational to liberation theology, suggesting that at least some of its central claims could survive translation to other conceptions.